The prevalence and characteristics associated with mother-infant bed-sharing in Klang district, Malaysia - Tan, K.L.; Ghani, S.N.; Moy, Foong Ming (Malaysian Medical Association, 2009)
This was a cross-sectional study to determine the prevalence and characteristics of mother-infant bed-sharing practice in Klang district, Malaysia. Data was collected by face-to-face interview using a structured questionnaire for a four month period in 2006. A total of 682 mother-infant pairs attending government health clinics were included in the study. Data regarding socio-demographic characteristics of the mothers, information on the infants, bed-sharing and breastfeeding practices were collected. The mean maternal age was 28.4 Â± 5.1 years while the mean infant gestational age was 38.8 Â± 1.8 weeks. The study showed the prevalence of bed-sharing was 73.5 (95 CI: 70.0, 76.7). In multivariate analysis; area of interview, maternal occupation, family income, breastfeeding and infant birth weight were associated with bed-sharing after adjusted for maternal ethnicity, age, marital status, educational level, parity, infant gender and infant gestational age. In conclusion, bed-sharing is a common practice in Klang district, Malaysia, not specific to ethnicity, but strongly associated with low family income and breastfeeding.